Sedimentary and tectonic breccias at the base of the Ediacaran Tamengo Formation (Corumbá Group): a comparative study - Fernandes,Henrique Albuquerque (2022)
Abstract The Corumbá Group is a Neoproterozoic succession of terrigenous and carbonate sedimentary rocks located at the southern Paraguay Belt, central Brazil. The upper units of the Corumbá Group include the Ediacaran carbonate Bocaina and Tamengo formations, whose limit is characterized by polymictic breccias recognized in several sites from Corumbá to Serra da Bodoquena, Mato Grosso do Sul. Despite the widespread occurrence, the breccias are poorly described and their origin is uncertain. The aim of this study is to present the differences between sedimentary and tectonic breccias of the Corumbá Group and propose a genesis model for each. The sedimentary breccias comprise mainly matrix-supported chaotic facies that formed by submarine mass flows on slope aprons. Sea level fall and/or increased faulting rates exposed the underlying units and triggered the gravity fluxes by creating a steep slope. The base of the sedimentary breccia represents a major unconformity within the carbonate sedimentation of the Corumbá Group, with potential correlation to other Ediacaran units. The subsequent development of the Paraguay fold-thrust belt caused the formation of tectonic breccias in reverse fault zones. Cataclasis and mylonitization deformed the dolomitic host rock by fracturing and produced a fine foliated matrix.